Introduction to statistical analysis of laboratory data - Bartolucci, Alfred (Wiley, 2015)
Introduction to Statistical Analysis of Laboratory Data presents a detailed discussion of important statistical concepts and methods of data presentation and analysis -Provides detailed discussions on statistical applications including a comprehensive package of statistical tools that are specific to the laboratory experiment process -Introduces terminology used in many applications such as the interpretation of assay design and validation as well as "fit for purpose" procedures including real world examples -Includes a rigorous review of statistical quality control procedures in laboratory methodologies and influences on capabilities -Presents methodologies used in the areas such as method comparison procedures, limit and bias detection, outlier analysis and detecting sources of variation -Analysis of robustness and ruggedness including multivariate influences on response are introduced to account for controllable/uncontrollable laboratory conditions.